Study on the Response of Qingyuan City's Water Consumption to the Adjustment of Industrial Structure and Policy - FENG Fangguan; XIONG Yujiu; FANG Yizhou (Renmin Zhujiang)
It is necessary to study characteristics of water resources consumptionand its response to adjustment of industrial structure and policies, which canprovide information for further adjusting and optimizing policies related to waterresources management. Taking Qingyuan city, Guangdong province as an example, thispaper reflects the impact of policy changes on the industrial structure throughthe GDP changes of three major industries, collects and analyzes the changes inthe water consumption structure of three major industries based on its waterconsumption of three major industries from 2006 to 2018 and other data, anddiscusses the response of water consumption and its structure to industrial policychanges in combination with the new round of industrial structure and policychange in 2008. The results show that:①The secondary and tertiary industries inQingyuan account for more than 80% of the total GDP and the primary industry(agriculture) contributes the remaining 20%, but the primary industry consumesmost of the water resources with a value greater than 80%;② Impacted by theecological-oriented policies of Qingyuan city, GDP of the secondary industry isdecreasing whereas it is increasing for the tertiary industry; ③ Waterconsumption of all the three industries changed a lot since 2012, i.e., theagricultural water consumption began to decline, with a value of approximately 200million cubic meters, and the water consumption of the secondary industry began todecrease, with a value of approximately 50 million cubic meters, and then increaseslightly; ④ Although the water consumption is declining, agriculture consumesmore than 80% of water resources, which mismatches its low contribution in GDP(less than 20%). It is concluded that there is still large space for adjustmentand optimization in agriculture in Qingyuan city.